Utilizing the Linguistic Landscape Feature of the Muslim Pro Application to Improve the Memorization Skills of Students at the Ar-Ridho Tahfidz House - Dewi Nurmala; Ayu Melati Ningsih; Muhammad Ferry Hidayat; Nasuha Ibnu Salam; Nazir Hidayat (Jurnal Pengabdian West Science, 2026)
This article is the result of the community service activity of a team of lecturers and students of Universitas Muslim Nusantara Al-Washliyah from the English literature study program to the students at the Ar-Ridho Tahfidz house. The purpose of this community service is to share knowledge of linguistic landscape labelling of business signboards. This Community Service (PkM) initiative aims to address the issues of declining motivation and slowing progress in memorization (ziyadah) among students at the Ar-Ridho Tahfidz House, caused by visual fatigue from conventional print media. The proposed solution is training and guidance on utilizing the digital linguistic landscape through the Muslim Pro app. This digital linguistic landscape includes optimizing the visual layout of Al-Qur’anic verses, color-coded tajwid cues (chromatic cues), and audio-text synchronization. The implementation method consists of three stages: (1) Orientation and installation, (2) Training on the use of visual memory features and self-directed audio controls, and (3) Periodic mentoring over the course of one month. The community service partners were 9 advanced-level students and 1 supervising teacher at the Ar-Ridho Tahfidz House. Program evaluation results showed a significant improvement in the students’ memorization skills. This community service activity demonstrates that targeted mobile technology interventions can accelerate traditional memorization methods.